Factors associated with coinfections in invasive aspergillosis: a retrospective cohort study. (November 2021) - Danion, François; Duval, Céline; Séverac, François; Bachellier, Philippe; Candolfi, Ermanno; Castelain, Vincent; Clere-Jehl, Raphaël; Denis, Julie; Dillenseger, Laurence; Epailly, Eric; Gantzer, Justine; Guffroy, Blandine; et al.
Abstract: Objectives: To describe the coinfections in invasive aspergillosis (IA), to identify factors associated with coinfections, and to evaluate the impact of coinfection on mortality. Patients and methods: We conducted a monocentric retrospective study of consecutive putative, probable, or proven IA that occurred between 1997 and 2017. All coinfections, with an onset within 7 days before or after the first sign of aspergillosis, were identified. Factors associated with coinfections and mortality were analysed by multivariable analysis. Results: Among the 690 patients with IA included in the study, the median age was 57 years (range 7 days to 90 years). A coinfection was diagnosed in 272/690 patients (39.4%, 95%CI 35.8–43.2). The location of this coinfection was pulmonary only in 131/272 patients (48%), bloodstream only in 66/272 patients (24%) and other/multiple sites in 75/272 patients (28%). Coinfections were bacterial (110/272 patients, 40%), viral (58/272, 21%), fungal (57/272, 21%), parasitic (5/272, 2%) or due to multiple types of pathogens (42/272, 15%). Factors associated with a coinfection in adjusted analysis were: allogeneic haematopoietic stem-cell transplantation (OR 2.3 (1.2–4.4)), other haematological malignancies (OR 2.1 (1.2–3.8)), other underlying diseases (OR 4.3 (1.4–13.6)), lymphopenia (OR 1.7 (1.1-2.5)), C-reactive protein >180 mg/L (OR 1.9 (1.2–3.0)), fever (OR 2.4 (1.5–4.1)), tracheal intubation (OR 2.6 (1.5–4.7)), isolation of two or more different Aspergillus species (OR 2.7 (1.1–6.3)), and the presence of non-nodular lesions on chest computed tomography (OR 2.2 (1.3–3.7) and OR 2.2 (1.2–4.0)). Coinfections were independently associated with a higher mortality at week 12 (adjusted HR 1.5 (1.1–1.9), p < 0.01). Conclusions: Coinfections are frequent in IA patients and are associated with higher mortality.